IMPLEMENTASI CHATBOT KONSELING ANAK BERBASIS DIALOGFLOW UNTUK PENCEGAHAN BULLYING - Pateman, Dimar; Zaliluddin, Dadan (Universitas Majalengka, 2025)
This study aims to design and implement a chatbot-based counseling service for children to prevent bullying, utilizing Dialogflow integrated with Telegram. The research addresses the limited access children have to report bullying cases and receive initial counseling, particularly in regions with constrained resources. The development applied the waterfall method, covering requirements analysis, system design, implementation, Testing, and maintenance. The chatbot provides three main features: counseling services, bullying reporting, and educational content. Black Box Testing and User Acceptance Testing (UAT) showed that all features function according to specifications, with positive user feedback on accessibility and usability. The integration of Dialogflow's Natural Language Processing (NLP) capabilities enables the chatbot to understand user intent and provide contextually relevant responses. The solution is expected to support the Dinas Pemberdayaan Perempuan, Perlindungan Anak, dan Keluarga Berencana (DP3AKB) in Majalengka in monitoring and handling bullying cases, while offering children a safe and interactive platform for reporting and education.